Interrelation of effective doze power with pollution density after accident at atomic reactor - Применко, В.І.; Канунніков, Б.Т.; Жижченко, О.П.; Пастухов, В.К.; Лук’янчиков, В.А. (Proceedings of National Aviation University (archive), 2005)
The analitical relation between doze power at control point taking into account the distance to the place of accident and contamination after accident on atomic reactor.